Dynamics of Taxpayer Awareness: Taxation Socialization, Taxpayer Attitude and Taxpayer Compliance as Moderating Variables - Atika Purnamasari; Popong Suryani; Yohanes August Goenawan (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: The study analyzes the influence of tax socialization and taxpayer attitudes on taxpayer awareness, and examines the role of taxpayer compliance as a moderating variable on MSMEs in Parahu-Sukamulya Village. Background of the Problem: The increasing number of entrepreneurs in the creative economy sector in reality does not have much effect on changes in the amount of tax payments to the State. Novelty: Analyzing the same variables but focusing on MSMEs in a region. Research Method: Using a quantitative method with a survey approach. Primary data was obtained through questionnaires distributed to MSMEs in the study area. Findings/Results: That tax socialization and taxpayer attitudes have a significant effect on taxpayer awareness. Conclusion: These findings provide important implications for tax authorities in designing strategies for socialization and increasing tax compliance in the MSME sector.